Association between HSV-2 and HIV serostatus in pregnant women of known HIV serostatus attending Mulago Hospital antenatal clinic, Kampala, Uganda - Nakubulwa, Sarah; Mirembe, Florence M.; Kaye, Dan K.; Kaddu-Mulindwa, Deogratias (The Journal of Infection in Developing Countries, 2009)
Background: Studies show that STIs such as HSV-2 increase the probability of HIV-1 acquisition and enhance transmission by increasing susceptibility and infectiousness respectively. The objective of this study was to compare the proportion of HSV-2 in HIV-positive and HIV-negative pregnant mothers attending the antenatal clinic in Mulago Teaching Hospital in Kampala, Uganda. Methods: This case control study included 50 pregnant women who were HIV positive and 200 controls of pregnant women who were HIV negative and were aware of their serostatus. Data was collected in two parts: the first part involved a pretested interviewer-administered semi-structured questionnaire for socio-demographic characteristics, sexual and behavioral history. The second part consisted of a serological test using an ELISA assay specific for IgG against viral glycoprotein G, specific to HSV-2. Results: The proportion of HSV-2 was 86% (43/50) among the HIV-positive cases and 62% (125/200) among the HIV-negative controls. The odds of being HSV-2 seropositive was 3.7 times higher (95% CI was 1.58 – 8.61) in HIV-positive cases than in the HIV negative controls. The odds of HSV-2 was significantly increased to 5.32 (95 CI was 1.92 – 14.73) among cases when adjustment was done for age, education, marital status, religion, age at first sexual experience, lifetime partners, type of earning, and whether the mother involved the partner in seeking treatment for sexually transmitted diseases. Conclusion: The proportion of HSV-2 was higher in HIV-positive cases than in the HIV negative controls.
Keywords: HSV-2; Pregnancy; Antenatal care; Prevalence; HIV infection